The Bureaucratisation of the National Gender Machinery, Circumventing the "Red Tape" - Ramparsad, Nitasha (HTS teologiese studies, 2019)
The bureaucratisation of the National Gender Machinery (NGM) in South Africa is discussed with a specific focus on documenting the historical formation thereof. This article addresses the barriers to implementation and explains the evolution of gender mainstreaming as a strategy for gender equality. Key recommendations for the effective use of the structures of the NGM are provided with an emphasis on an integrated strategy for the furtherance of gender equality within the South African public service.